Endovascular Stent Reconstruction of the Inferior Vena Cava Complicated by Duodenocaval Fistula - Hamblin, James (Thieme Medical Publishers, 2011)
A patient with retroperitoneal metastatic uterine adenocarcinoma resulting in symptomatic occlusion of the inferior vena cava underwent palliative endovascular stent reconstruction and subsequent radiation therapy. She then developed sepsis and massive lower gastrointestinal bleeding. Computed tomography (CT) and cavography demonstrated a fistulous communication between the duodenum and the stented segment of inferior vena cava. Deployment of endovascular stent graft devices successfully occluded the fistulous communication and resulted in clinical improvement.